2022
DOI: 10.1111/jog.15186
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 polymorphism contributes to the genetic susceptibility of epithelial ovarian cancer

Abstract: Aim Cytotoxic T‐lymphocyte antigen‐4 (CTLA‐4), an inhibitory molecule on T‐cells, plays a key role in tumorigenesis and progression. In the present study, we investigated the effects of three polymorphisms in the CTLA‐4 gene on the risk of epithelial ovarian cancer and the clinical outcomes of patients. Methods A case–control study was performed in 527 epithelial ovarian cancer patients and 532 controls. Genotypes of three polymorphisms were determined by polymerase chain reaction/ligase detection reaction. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…However, no significant correlation was detected between the rs231775 G/A and rs3087243 G/A polymorphisms and susceptibility to EOC. The results confirmed that in women, the CTLA-4 rs5742909 C/T polymorphism may decrease the genetic predisposition to EOC ( 183 ).…”
Section: The Potential Of Antitumor Therapy On the Immune Microenviro...supporting
confidence: 79%
“…However, no significant correlation was detected between the rs231775 G/A and rs3087243 G/A polymorphisms and susceptibility to EOC. The results confirmed that in women, the CTLA-4 rs5742909 C/T polymorphism may decrease the genetic predisposition to EOC ( 183 ).…”
Section: The Potential Of Antitumor Therapy On the Immune Microenviro...supporting
confidence: 79%
“…Another co-inhibitory molecule that plays a crucial role in OC progression and tumorigenesis is CTLA-4 [ 35 ]. It is a membrane protein expressed by activated T cells, constitutively regulatory T cells (Tregs), and is considered to be homologous to CD28, which is involved in the second step of T cell activation after the binding of an antigen and T cell receptor (TCR).…”
Section: Treatment Of Ovarian Cancermentioning
confidence: 99%
“…CTLA-4 is a T-cell inhibitory molecule who has a significant impact in carcinogenesis and progression [88]. CTLA-4 reduces the antitumor immune response mediated by T lymphocytes by inhibiting cytokine receptor signals, protein translation, triggering ubiquitin ligases, & mobilizing phosphatases [89].…”
Section: Cytotoxic T-lymphocyte Antigen-4 (Ctla-4)mentioning
confidence: 99%